ZENK Induction in the Zebra Finch Brain by Song: Relationship to Hemisphere, Rhythm, Estradiol, and Sex - Lampen, Jennifer (J Neuroendocrinol, 2017)
Estradiol is abundant in the zebra finch auditory forebrain and has the capacity to modulate neural responses to auditory stimuli with specificity due to both hemisphere and sex. Arrhythmic song induces greater ZENK expression than rhythmic song in the caudomedial nidopallium (NCM), caudomedial mesopallium (CMM), and nucleus taeniae (Tn) of adult zebra finches. The increases in the auditory regions, NCM and CMM, may result from detection of errors in the arrhythmic song relative to the learned template. In the present study, zebra finches were treated with estradiol, the aromatase inhibitor fadrozole, or a control, and exposed to rhythmic or arrhythmic song to assess the effect of estradiol availability on neural responses to auditory rhythms. ZENK mRNA was significantly greater in the left hemisphere within NCM, CMM, and Tn. Main effects of sex were detected in both auditory regions, with increased ZENK in males in NCM and in females in CMM. In CMM, an effect of hormone treatment also existed. While no pairwise comparison was statistically significant, the pattern suggested greater ZENK expression in control compared to both fadrozole- and estradiol-treated birds. In NCM, an interaction between sex and hormone treatment suggested that the sex effect was restricted to control animals. An additional interaction in NCM among sex, stimulus rhythmicity, and hemisphere indicated that the strongest effect of laterality was present in males exposed to arrhythmic song. The hormone effects suggest that an optimal level of estradiol may exist for processing rhythmicity of auditory stimuli. The overall pattern for left lateralization parallels the left lateralization of language processing in humans and may suggest that this hemisphere is specialized for processing conspecific vocalizations. The reversed sex differences in NCM and CMM suggest that males and females differentially rely on components of the auditory forebrain for processing conspecific song.